MPPT using novel FLC based MPO for photovoltaic system - R. Arulmurugan (Institute of Advanced Engineering and Science, 2019)
In this paper introduces a novel Fuzzy Logic Controller (FLC) as a Maximum Power Extracting (MPE) of photovoltaic standalone system is proposed, which can handle the uncertainties of the rules under high deviations in climate conditions. Conventional Perturb and Observe (P & O), hill-climbing MPE structures are examined. The MPE employed boost converter controller. The new controller improves P & O based maximum power tracker search method by rules fuzzifying of such method and eliminates the conventional drawback. A new FLC based improved P & O offers an accurate and fast converging to MPE during steady state and changing climatic situation compared to existing P & O and hill climbing method. The performance of the designed MPE is demonstrated in simulation MATLAB at dissimilar operating circumstances.